Eupotemus tuberculatus sp. nov., the first hooded shore beetle confirmed from southern Africa (Coleoptera, Epimetopidae) - Bilton, David T.; Bird, Matthew S. (Zootaxa, 2023)
Eupotemus tuberculatus sp. nov. is described on the basis of two specimens discovered during recent field work in South Africa. This is the first member of the Epimetopidae to be confirmed in Africa south of the Congo Basin and Tanzania. The new species is a member of the Eupotemus carinaticollis Fikáček et al., 2021 species group, sharing features of pronotal and aedeagal design. Characters distinguishing the new species from previously described taxa are discussed and notes provided on the collecting circumstances.